The stress regulator FKBP51: a novel and promising druggable target for the treatment of persistent pain states across sexes - Maiarù, Maria (Pain, 2018)
It is well established that FKBP51 regulates the stress system by modulating the sensitivity of the glucocorticoid receptor to stress hormones. Recently, we have demonstrated that FKBP51 also drives long-term inflammatory pain states in male mice by modulating glucocorticoid signalling at spinal cord level. Here, we explored the potential of FKBP51 as a new pharmacological target for the treatment of persistent pain across the sexes. First, we demonstrated that FKBP51 regulates long-term pain states of different aetiologies independently of sex. Deletion of FKBP51 reduced the mechanical hypersensitivity seen in joint inflammatory and neuropathic pain states in female and male mice. Furthermore, FKBP51 deletion also reduced the hypersensitivity seen in a translational model of chemotherapy-induced pain. Interestingly, these 3 pain states were associated with changes in glucocorticoid signalling, as indicated by the increased expression, at spinal cord level, of the glucocorticoid receptor isoform associated with glucocorticoid resistance, GR(β), and increased levels of plasma corticosterone. These pain states were also accompanied by an upregulation of interleukin-6 in the spinal cord. Crucially, we were able to pharmacologically reduce the severity of the mechanical hypersensitivity seen in these 3 models of persistent pain with the unique FKBP51 ligand SAFit2. When SAFit2 was combined with a state-of-the-art vesicular phospholipid gel formulation for slow release, a single injection of SAFit2 offered pain relief for at least 7 days. We therefore propose the pharmacological blockade of FKBP51 as a new approach for the treatment of persistent pain across sexes, likely in humans as well as rodents.